Respuesta :
Answer:
r = 4b + 3
Step-by-step explanation:
given equation 16b = 4r - 12
in function notation, dependent variable should be on the right n independent variable appears on the left
16b + 12 = 4r - 12 +12
16b + 12 = 4r
flip left n right
4r = 16b + 12
divide by 4
r= 4b + 3
Answer:
r = 4b + 3
Step-by-step explanation:
As b is the independent variable, r must be the dependent variable which should be on the left by itself in function notation.
Rearranging 16b = 4r - 12
4r = 16b + 12
r = 4b + 3